Langkah Mudah Pembuatan Sistem Informasi Berbasis Android Bagi Pemula - Jems Yohanis Solle; Uminingsih Uminingsih (Jurnal Teknologi, 2021)
The need to get information in any form becomes important. Along with that, people who want to provide information are increasing day by day, both specific information (accessed for certain circles only) or general information systems (all people can access it). The problem is how to make an information system that can be accessed by android mobile phones faster and easier by beginners. An information system that can be accessed via Android phones is very practical and profitable because it can be accessed anywhere and anytime as long as you get an internet signal at that time. The difficulty in making an information system model like this is because many elements must be done, such as: installing some software, which takes time to learn from each of the built-in tools, providing a database, creating interfaces, and connecting the system to the cellphone. This study presents the result how to create an Android-based information system that is systematic and easy for beginners in the form of instructions for the steps of making a system which is equipped with a display capture of the installation activity results from several supporting software and is equipped with examples of the results of information system designs that have been successfully created. It is hoped that the results of this research can help make it easier to design an Android-based Information system application for beginners.